Metabolic side effects in persons with schizophrenia during mid‐ to long‐term treatment with antipsychotics: a network meta‐analysis of randomized controlled trials. Issue 1 (14th January 2023) - Burschinski, Angelika; Schneider‐Thoma, Johannes; Chiocchia, Virginia; Schestag, Kristina; Wang, Dongfang; Siafis, Spyridon; Bighelli, Irene; Wu, Hui; Hansen, Wulf‐Peter; Priller, Josef; Davis, John M.; Salanti, Georgia; et al.
Abstract : Metabolic side effects of antipsychotic drugs can have serious health consequences and may increase mortality. Although persons with schizophrenia often take these drugs for a long time, their mid‐ to long‐term metabolic effects have been studied little so far. This study aimed to evaluate the mid‐ to long‐term metabolic side effects of 31 antipsychotics in persons with schizophrenia by applying a random‐effects Bayesian network meta‐analysis. We searched the Cochrane Schizophrenia Group's Study‐Based Register of Trials (up to April 27, 2020) and PubMed (up to June 14, 2021). We included published and unpublished, open and blinded randomized controlled trials with a study duration >13 weeks which compared any antipsychotic in any form of administration with another antipsychotic or with placebo in participants diagnosed with schizophrenia. The primary outcome was weight gain measured in kilograms. Secondary outcomes included "number of participants with weight gain", fasting glucose, total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, and triglycerides. We identified 137 eligible trials (with 35, 007 participants) on 31 antipsychotics, with a median follow‐up of 45 weeks. Chlorpromazine produced the most weight gain (mean difference to placebo: 5.13 kg, 95% credible interval, CrI: 1.98 to 8.30), followed by clozapine (4.21 kg, 95% CrI: 3.03 to 5.42), olanzapine (3.82 kg, 95% CrI: 3.15 to 4.50), and zotepine (3.87 kg, 95% CrI: 2.14 to 5.58). The findings did not substantially change in sensitivity and network meta‐regression analyses, although enriched design, drug company sponsorship, and the use of observed case instead of intention‐to‐treat data modified the mean difference in weight gain to some extent. Antipsychotics with more weight gain were often also among the drugs with worse outcome in fasting glucose and lipid parameters. The confidence in the evidence ranged from low to moderate. In conclusion, antipsychotic drugs differ in their propensity to induce metabolic side effects in mid‐ to long‐term treatment. Given that schizophrenia is often a chronic disorder, these findings should be given more consideration than short‐term data in drug choice.